INFLUENCE OF PLANT GROWTH REGULATORS ON SEEDLINGS MORPHOGENESIS AND LABORATORY SEED GERMINATION OF WINTER PEA OF VARIETY NS MOROZ - Shevchuk V. V. (Вісник Уманського національного університету садівництва, 2019)
The introduction of winter pea into the agricultural production is a priority direct of the plant growing because of a several advantages of winter pea over the spring pea: regular harvest of grain and green mass; protection of soil from wind and water erosion; effective use of moderate temperatures and humidity of late autumn and early spring periods. The purpose of our work was to show the results of studies of the influence of growth regulators on the laboratory seed germination and morphometric parameters of seedlings of winter pea. The studies were conducted on the culture of winter pea of variety NS Moroz. Presowing treatment of pea seeds was performed with aqueous solutions of Gumifild (0,2 %) and Endophyt-L1 (0,2 %), and with water in the control. In the process of research, the germination energy and laboratory germination of seeds, the linear sizes of the hypocotyl and the main root of the seedlings, the dry mass of seedlings and roots were determined. It was established that preparations Endophyt-L1 and Gumifild increased the laboratory germination of the seed and germination energy. Under the influence of the drug Endophyt-L1 germination energy increased by 12 % and laboratory germination of seeds – by 8 %. The application of Gumifild was more efficient, because the germination energy in this experimental variant increased by 16 % and the general germination of seeds – by 11 %. The number of normally developed seedlings (with a length of 0,5-1,0 cm) in the variant with the using of Endophyt-L1 was 42,8, with the using of Gumifild – 46. There were 36,2 seedlings in control. It was established that the use of the drugs of stimulating action has led to changes in the morphogenesis of seedlings of winter pea culture. The preparations caused the lengthening of the hypocotyl and the main root of the young plants. Growth regulators increased the damp weight of hypocotyls and roots of the winter pea seedlings. The best effect was found in the pre-sowing treatment of seeds with Gumifild (0,2 %). When comparing the two used preparations, it should be noted that the application of the natural plant growth stimulator Gumifild on the seeds of winter pea of variety of NS Moroz was more effective than the using of the broad-spectrum plant growth stimulator Endophyt-L1. The search of the ways to increase the level of productivity of winter peas aimed at the study of technology of cultivation of Frost variety with the introduction of new methods and the use of plant growth regulators with different mechanisms of action and inoculation by symbiotic bacteria.